Structural Neural Correlates of Double Decision Performance in Older Adults - Kraft, Jessica N.; O’Shea, Andrew; Albizu, Alejandro; Evangelista, Nicole D.; Hausman, Hanna K.; Boutzoukas, Emanuel; Nissim, Nicole R.; Van Etten, Emily J.; Bharadwaj, Pradyumna K.; Song, Hyun; Smith, Samantha G.; Porges, Eric; et al. (Frontiers in Aging Neuroscience, 2020)
Speed of processing is a cognitive domain that encompasses the speed at which an individual can perceive a given stimulus, interpret the information, and produce a correct response. Speed of processing has been shown to decline more rapidly than other cognitive domains in an aging population, suggesting that this domain is particularly vulnerable to cognitive aging (Chee et al., 2009). However, given the heterogeneity of neuropsychological measures used to assess the domains underpinning speed of processing, a diffuse pattern of brain regions has been implicated. The current study aims to investigate the structural neural correlates of speed of processing by assessing cortical volume and speed of processing scores on the POSIT Double Decision task within a healthy older adult population (N= 186; mean age= 71.70 +- 5.32 years). T1-weighted structural images were collected via a 3T Siemens scanner. The current study shows that less cortical thickness in right temporal, posterior frontal, parietal and occipital lobe structures were significantly associated with poorer Double Decision scores. Notably, these include the lateral orbitofrontal gyrus, precentral gyrus, superior, transverse, and inferior temporal gyrus, temporal pole, insula, parahippocampal gyrus, fusiform gyrus, lingual gyrus, superior and inferior parietal gyrus and lateral occipital gyrus. Such findings suggest that speed of processing performance is associated with a wide array of cortical regions that provide unique contributions to performance on the Double Decision task.